Creación de objetos de aprendizaje en el área de matemáticas para estudiantes del octavo año de educación general básica. - Pilco Barahona, Geovanny Javier (2022)
ABSTRACT: During mathematics learning, concepts are not often re-presented, nor is it allowed to predict facts, situations, and results. In general, it has based only on operating through the memorization of data, which implies that they had quickly forgotten in the long term. Due to those mentioned above, the present research work aims to create a Learning Object applied to the area of Mathematics for eighth-year students of Basic General Education as a proposal for teaching-learning and strengthening cognitive skills. The development methodology for creating the Learning Object is based on the DICREVOA 2.0 methodology, formulated in 5 steps: Analysis, Design, Implementation, Evaluation, and Publication. It was essential to know the technical and pedagogical requirements to address the Learning Object according to the needs of the students. It has concluded then that this work, based on the bibliographical inquiry, it has consulted for the eighth year of Basic General Education. It had managed to define that reasoning, analysis, and deduction are cognitive skills as training objectives that need to be strengthened with the practice of activities where permanent digital scenarios have been proposed, as is the case of the Learning Objects.